New representatives of Pseudomonas genus from Antarctic soils - O. I. Kotsoflyak (Ukrainian Antarctic Journal, 2006)
59 strains of pseudomonads have been isolated from soil, moss and silt of Galindes, Piterman and Deseption islands. 113 phenotypic characteristics were studied for these strains and using computer analysis 25 strains were identified as representatives of Pseudomonas fluorescens biovar V, 22 – as P.putida biovars A and B, 2 – as P. alcalifilai. Results of 16 S rRNA sequence and phenotypic analysis allowed to identify 8 antarctic isolates as P.veronii and P. fragi and have shown belonging of 2 non-identified strains to P. fluorescens – complex. Obtained data give evidence, that Antarctic bacteria include both the widespread and exotic, probably new species of pseudomonads.